Starch hydrolyses and laccase activity of heat tolerant mushroom isolate - Shalaby , Moustafa E.; El-Khateeb, Nagwa M.; Óbert, Mária; Posta, Katalin (JOURNAL OF LANDSCAPE ECOLOGY, 2013)
34 isolates of oyster mushroom recovered from different regions of Egypt were screened on the bases of their growth rate at different temperatures. Only five isolates were able to growth intensively at 35 ºC and isolate P1 together with P2 showed the highest growth rate. According to morphological and cultural characteristics of two tested mushroom isolates both belonged to Pleurotus ostreatus species. Besides measuring their growth rates under wide range of temperatures (18ºC, 28ºC, 35ºC and 40ºC) the ability of starch hydrolyses was also tested. Isolate P1 showed almost same hydrolysis rates, however there was a steady increase in hydrolyses of starch by isolate P2 which began to decline over 35°C. Some mushrooms produce not only hydrolytic but also oxidative enzymes, such as laccase. After 15 days of growing isolate P2 showed high laccase activity at 35ºC suggesting that this heat tolerant isolate could be a good candidate for various industrial applications or mushroom producers in Egypt.
Keywords: Pleurotus ostreatus; starch hydrolysis; laccase; heat tolerant